Data Sheet 1_Water chemistry of Alaskan glacial rivers is affected by glacier coverage, bedrock type, and groundwater inputs.pdf - Miaja Coombs; Gregory T. Carling; Lee Ann Munk; Jordan Jenckes; Barry R. Bickmore; Kevin A. Rey; Alyssa N. Thompson; Diego P. Fernandez; Anna Bergstrom; Teresa Gomez (2025)
Glacial meltwater contributions to streams depend on watershed characteristics that impact water quantity and quality, with potential changes as glaciers continue to recede. The purpose of our study was to investigate the influence of glacier and bedrock controls on water chemistry in glacial streams, focusing on a range of small to large watersheds in Alaska. Southcentral Alaska provides an ideal study area due to diverse geologic characteristics and varying amounts of glacial coverage across watersheds. To investigate spatial and temporal variability due to glacial coverage and bedrock type, we analyzed water samples (n = 343) from seven watersheds over 2 years for major and trace element concentrations and water stable isotopes. We found variable water chemistry across the glacial rivers related to glacial coverage and the relative amount of metamorphic, sedimentary, and igneous bedrock. Some sites had elevated concentrations of harmful trace elements like As and U from glacier melt or groundwater. Longitudinal (upstream to downstream) variability was apparent within each river, with increasing inputs from tributaries, and groundwater altering the water chemistry relative to glacier meltwater contributions. The water chemistry and isotopic composition of river samples compared with endmember sources suggested a range from glacier-dominated to groundwater-dominated sites along stream transects. For example, water chemistry in the Knik and Matanuska rivers (with large contributing glaciers) was more influenced by glacier meltwater, while water chemistry in the Little Susitna River (with small glaciers) was more influenced by groundwater. Across all rivers, stream chemistry was controlled by glacier inputs near the headwaters and groundwater inputs downstream, with the water chemistry reflecting bedrock type. Our study provides a greater understanding of geochemical and hydrological processes controlling water resources in rapidly changing glacial watersheds.